Accuracy of height and weight data from child health records. Issue 12 (17th August 2009) - Howe, L D; Tilling, K; Lawlor, D A
Abstract : Background: There is limited knowledge of the accuracy of height and weight measurements from child health records, despite widespread use for research and clinical care. We assess the accuracy of such measurements, using research measurements as the gold standard. Methods: We compare height/length and weight measurements from clinics of the Avon Longitudinal Study of Parents and Children with routinely collected child health records within 2 months of the clinic date at age 4 (n = 345), 8 (n = 1051), 12 (n = 139), 18 (n = 649), 25 (n = 183), and 43 months (n = 123). To adjust for age differences at measurement, growth data were converted into standard deviation scores using the UK 1990 growth reference. Results: Mean weight standard deviation score (SDS) differences were ⩽0.08, with mean predicted differences ⩽0.1 kg (eg, mean predicted difference at 8 months −0.011 kg, 95% level of agreement −0.64 to 0.62 kg). Mean height SDS differences were ⩽0.45, with mean predicted differences ⩽0.9 cm (eg, mean predicted difference at 8 months −0.59 cm, 95% level of agreement −3.84 to 2.66 cm). There was indication of lower accuracy at 4 months old (mean predicted height difference at 4 months −0.91 cm, 95% level of agreement −4.61 to 2.79 cm), but this decreased when the age difference between measurements was reduced. Routine measurements slightly overestimated heights of tall children and underestimated those of short children, but otherwise differences were not associated with sex, social class, birth weight, birth length, or maternal anthropometry. Conclusion: Routinely collected child health record height/length and weight data are compatible with no systematic bias, at least in children over 8 months old, supporting their use in clinical practice and research.